Targeted deep amplicon sequencing of antimalarial resistance markers in Plasmodium falciparum isolates from Cameroon. (June 2021) - L'Episcopia, Mariangela; Kelley, Julia; Djeunang Dongho, Bruna G.; Patel, Dhruviben; Schmedes, Sarah; Ravishankar, Shashidhar; Perrotti, Edvige; Modiano, David; Lucchi, Naomi W.; Russo, Gianluca; Talundzic, Eldin; Severini, Carlo
Graphical abstract: Highlights: Artemisinin-based combination therapy for the treatment of malaria cases in Cameroon. Drug resistance remains one of the greatest challenges of malaria control. Next-generation sequencing is an effective method for monitoring drug-resistant Plasmodium falciparum parasites. Artemisinin-based combination therapy is still effective in Cameroon. The high prevalence of dhps / dhfr mutations suggests active surveillance of sulfadoxine-pyrimethamine efficacy is important. Abstract: Background: Recent studies showed the first emergence of the R561H artemisinin-associated resistance marker in Africa, which highlights the importance of continued molecular surveillance to assess the selection and spread of this and other drug resistance markers in the region. Method: In this study, we used targeted amplicon deep sequencing of 116 isolates collected in two areas of Cameroon to genotype the major drug resistance genes, k13, crt, mdr1, dhfr, and dhps, and the cytochrome b gene ( cytb ) in Plasmodium falciparum . Results: No confirmed or associated artemisinin resistance markers were observed in Pfk13 . In comparison, both major and minor alleles associated with drug resistance were found in Pfcrt, Pfmdr1, Pfdhfr, and Pfdhps . Notably, a high frequency of other nonsynonymous mutations was observed across all the genes, except for Pfcytb, suggesting continued selection pressure. Conclusions: The results from this study supported the continued use of artemisinin-based combination therapy and administration of sulfadoxine-pyrimethamine for intermittent preventive therapy in pregnant women, and for seasonal chemoprevention in these study sites in Cameroon.